Primary Chemoablation of Low-Grade Intermediate-Risk Nonmuscle-Invasive Bladder Cancer Using UGN-102, a Mitomycin-Containing Reverse Thermal Gel (Optima II): A Phase 2b, Open-Label, Single-Arm Trial. Issue 1 (26th January 2022) - Chevli, K. Kent; Shore, Neal D.; Trainer, Andrew; Smith, Angela B.; Saltzstein, Daniel; Ehrlich, Yaron; Raman, Jay D.; Friedman, Boris; D'Anna, Richard; Morris, David; Hu, Brian; Tyson, Mark; et al.
Abstract : Purpose: Low-grade intermediate-risk nonmuscle-invasive bladder cancer (LG IR NMIBC) is a recurrent disease, thus requiring repeated transurethral resection of bladder tumor under general anesthesia. We evaluated the efficacy and safety of UGN-102, a mitomycin-containing reverse thermal gel, as a primary chemoablative therapeutic alternative to transurethral resection of bladder tumor for patients with LG IR NMIBC. Materials and Methods: This prospective, phase 2b, open-label, single-arm trial recruited patients with biopsy-proven LG IR NMIBC to receive 6 once-weekly instillations of UGN-102. The primary end point was complete response (CR) rate, defined as the proportion of patients with negative endoscopic examination, negative cytology and negative for-cause biopsy 3 months after treatment initiation. Patients with CR were followed quarterly up to 12 months to assess durability of treatment effect. Safety and adverse events were monitored throughout the trial. Results: A total of 63 patients (38 males and 25 females 33–96 years old) enrolled and received ≥1 instillation of UGN-102. Among the patients 41 (65%) achieved CR at 3 months, of whom 39 (95%), 30 (73%) and 25 (61%) remained disease-free at 6, 9 and 12 months after treatment initiation, respectively. A total of 13 patients had documented recurrences. The probability of durable response 9 months after CR (12 months after treatment initiation) was estimated to be 73% by Kaplan-Meier analysis. Common adverse events (incidence ≥10%) included dysuria, urinary frequency, hematuria, micturition urgency, urinary tract infection and fatigue. Conclusions: Nonsurgical primary chemoablation of LG IR NMIBC using UGN-102 resulted in significant treatment response with sustained durability. UGN-102 may provide an alternative to repetitive surgery for patients with LG IR NMIBC.